Identification of caffeoylquinic acid derivatives as natural protein tyrosine phosphatase 1B inhibitors from Artemisia princeps - Zhang, Jie; Sasaki, Tatsunori; Li, Wei; Nagata, Kazuya; Higai, Koji; Feng, Feng; Wang, Jian; Cheng, Maosheng; Koike, Kazuo (Bioorganic & medicinal chemistry letters, 2018)
[Display omitted] •Caffeoylquinic acid derivatives are natural PTP1B inhibitors.•Chlorogenic acid showed potent PTP1B inhibitory activity.•Chlorogenic acid is a noncompetitive inhibitor.•Chlorogenic acid binds to the allosteric site of PTP1B. Considerable attention has been paid to protein tyrosine phosphatase 1B (PTP1B) inhibitors as a potential therapy for diabetes, obesity, and cancer. Ten caffeoylquinic acid derivatives (1–10) from leaves of Artemisia princeps Pamp. (Asteraceae) were identified as natural PTP1B inhibitors. Among them, chlorogenic acid (3) showed the most potent inhibitory activity (IC50 11.1 μM). Compound 3 was demonstrated to be a noncompetitive inhibitor by a kinetic analysis. Molecular docking simulation suggested that compound 3 bound to the allosteric site of PTP1B. Furthermore, compound 3 showed remarkable selectivity against four homologous PTPs. According to these findings, compound 3 might be potentially valuable for further drug development.